Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

4(2x + 1) -3 = -3(x – 4) Show your work

Sagot :

Answer:

x = 1

Step-by-step explanation:

4(2x + 1) - 3 = - 3(x - 4) ← distribute parenthesis on both sides

8x + 4 - 3 = - 3x + 12

8x + 1 = - 3x + 12 ( add 3x to both sides )

11x + 1 = 12 ( subtract 1 from both sides )

11x = 11 ( divide both sides by 11 )

x = 1